To kneel or not to kneel: Appropriating a religious and sport symbol for racial justice in South Africa - D. Andrew (Acta Theologica)
The act of kneeling of the Black Lives Matter Movement (BLM) has its origin in both the religious and the sport environment. In some religious circles it is believed that kneeling is a form of submission to God and in other circles it is a symbol of resistance to oppressive and dehumanising practices and structures. This article intends to investigate critically the use of the symbolism of kneeling, its socio-political and religious implications, how it is appropriated to address racism and other inequalities in sport, and how it can become a symbol in the process of achieving racial justice. The purpose of the study is to investigate whether the BLM concept of taking the knee (as well as the related expression “I can’t breathe”) and its ambiguous interpretation can be appropriated in the South African context and whether it can assist the struggle to achieve racial justice in South Africa. The study will follow a multidisciplinary approach and will utilise comparative literature analysis.